Is cardiac autonomic modulation influenced by beta blockers in adolescents with Duchenne Muscular Dystrophy? - Silva-Magalhães Talita Dias da; Moraes Íbis Ariana Peña de; Vanderlei Luiz Carlos Marques; Monteiro Carlos Bandeira de Mello; Silva Marcela Maria Carvalho da; Pereira Fernando; Dias Rodrigo Martins; Garner David; Grossklauss Luis Fernando; Dias de Carvalho Tatiana; Ferreira Celso (Translational Exercise Biomedicine)
As the Duchenne Muscular Dystrophy (DMD) is a progressive neuromuscular disorder frequently associated with cardiac dysfunction, this study aimed to evaluate the influence of beta-blocker therapy on cardiac autonomic modulation in adolescents with DMD by analyzing heart rate variability (HRV) indices in patients with and without beta-blockers.